2017
DOI: 10.1002/jhet.2790
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Utility of Pyridinium Bromide: Synthesis and Antimicrobial Activity of Novel 2,4,6‐Trisubstituted Pyridines Having Pyrazole Moiety

Abstract: Fourteen potentially bioactive pyridines, pendant to pyrazole moiety, were synthesized and evaluated in vitro for their antimicrobial potential. Treatment of 2‐bromo‐1‐(5‐methyl‐1‐phenyl‐1H‐pyrazol‐4‐yl)ethanone with pyridine afforded the corresponding pyridinium bromide salt. Reaction of the latter salt with α,β‐unsaturated ketones yielded the corresponding 2,4,6‐trisubstituted pyridine derivatives. The structures of the synthesized products were confirmed by all possible spectral data. The antimicrobial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Thienopyridines are considered as a class of the most important fused pyridines that reported as drugs, for example, Prasugrel , ticlopidine, and clopidogrel , in addition to irreversible ADP receptor/P2Y12 inhibitors that were used as an antiplatelet agent . Thienopyridines are reported as anticancer , antibacterial , antifungal , anti‐inflammatory , and antimicrobial agents . In view of these findings and in continuation of our previous work on pyridine and thienopyridine chemistry , we report herein facial synthetic approaches for new series of substituted and condensed pyridines.…”
Section: Introductionmentioning
confidence: 80%
“…Thienopyridines are considered as a class of the most important fused pyridines that reported as drugs, for example, Prasugrel , ticlopidine, and clopidogrel , in addition to irreversible ADP receptor/P2Y12 inhibitors that were used as an antiplatelet agent . Thienopyridines are reported as anticancer , antibacterial , antifungal , anti‐inflammatory , and antimicrobial agents . In view of these findings and in continuation of our previous work on pyridine and thienopyridine chemistry , we report herein facial synthetic approaches for new series of substituted and condensed pyridines.…”
Section: Introductionmentioning
confidence: 80%
“…Thus, treatment of the bromide salt 165 with benzalacetophenone 166a in acetic acid in the presence of ammonium acetate at reflux condition resulted in the formation of the novel 2‐(5‐methyl‐1‐phenyl‐1 H ‐pyrazol‐4‐yl)‐4,6‐diphenylpyridine ( 167 ) in 78% yield (Scheme ). In a similar way, the bromide salt 165 reacted with several chalcones 166b–n under similar experimental reaction condition to afford the corresponding 2,4,6‐trisubstituted pyridines 167b–n , as illustrated in Scheme .…”
Section: Chemistry Of 4‐acetyl‐1h‐pyrazolesmentioning
confidence: 98%
“…The active derivatives bear Cl À and F À in addition to aromatic substituents. [50] Compounds containing py as a substituent are accessible in laboratory with excellent yield but the antimicrobial efficiency needs further improvement. [51] From the list of compounds provided in Figure 5 with summarized activity against certain strains in Table 2, it can be observed that these compounds have extra potentials to emerge as antimicrobial agents in future.…”
Section: Antimicrobial Evaluationmentioning
confidence: 99%